The Effect of Environmental, Social, and Governance (ESG) Performance on Firm Value with Managerial Ownership and Profitability as Moderating Variables: (An Empirical Study on Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2021–2024) - Rahradisya Delvia Putri; Iis Ismawati; Ayu Noorida Soerono (PT Larva Wijaya Penerbit, 2026)
This study is motivated by the inconsistent empirical evidence regarding the effect of Environmental, Social, and Governance (ESG) performance on firm value, particularly in the energy sector. This study aims to examine the effect of ESG performance on firm value, with managerial ownership and profitability as moderating variables. The sample consists of 121 energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Using a quantitative approach, this study employs secondary data obtained from annual reports and sustainability reports. The data were analyzed using SPSS version 25 through descriptive statistical analysis, classical assumption tests, and hypothesis testing. The results indicate that ESG performance has a significant negative effect on firm value, while managerial ownership and profitability have a significant positive effect on firm value. Furthermore, managerial ownership and profitability moderate the relationship between ESG performance and firm value by weakening the negative effect of ESG performance on firm value. These findings suggest that managerial ownership and profitability play an important role in mitigating the adverse impact of ESG performance on firm value in energy sector companies